The stuff of the gods (Stockholm)
248 sayfa
Keywords: ''The “material turn“ in the humanities and social sciences has brought about an expanded understanding of the material dimension of all cultural and social phenomena. In the Classics it has resulted in the breaking down of boundaries within the discipline and a growing interest in materiality within literature'' -- Yayıncı.